The Effect of Debt to Equity Ratio, Cash Holding, Firm Size, and Corporate Social Responsibility Disclosure on Corporate Value - Aisy, Siti Nur Rohadatul; Surjandari, Dwi Asih (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2021)
The aim of this study is to examine the Debt to Equity Ratio, Cash holding, Firm Size, and Corporate Social Responsibility disclosure on corporate value of mining corporation listed in indonesia stock exchange on 2017 – 2018. This research using purposive sampling techniques based on determined criterias. Data collection used in this study is literature study with quantitative approach. The population of this research is all of mining corporation listed in indonesian stock exchange with 51 companies for the sample. The independent variables in this research are Debt to Equity Ratio(DER), Cash holding(CH), Firm Size(FS), and Corporate Social Responsibility disclosure(CSR) also Corporate Value(PBV) as dependent variable. This research data analysis using multiple linear regression using Eviews 11 aplication. The result shows that Debt to Equity Ratio, Cash Holding, Firm Size, dan CSR have significant effects on corporate value simultantly and Debt to Equity Ratio have significant effects on corporate value partially.